2015
DOI: 10.1242/jcs.164848
|View full text |Cite
|
Sign up to set email alerts
|

TM9 family proteins control surface targeting of glycine-rich transmembrane domains

Abstract: TM9 family proteins (also named Phg1 proteins) have been previously shown to control cell adhesion by determining the cell surface localization of adhesion proteins such as the Dictyostelium SibA protein. Here, we show that the glycine-rich transmembrane domain (TMD) of SibA is sufficient to confer Phg1A-dependent surface targeting to a reporter protein. Accordingly, in Dictyostelium phg1A-knockout (KO) cells, proteins with glycine-rich TMDs were less efficiently transported out of the endoplasmic reticulum (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…During the infection course, we identified an early response consisting in the upregulation of transcription of a large collection of phagocytosis and lysosome related genes (phg1A, AlyA, B, C, D) (Perrin et al, 2015). In addition, consistent with the report that ESCRT plays an important role in membrane repair during M. marinum infection, many of the ESCRT components were induced .…”
Section: Marinum Infection Induces a Damage And Stress Response Insupporting
confidence: 83%
“…During the infection course, we identified an early response consisting in the upregulation of transcription of a large collection of phagocytosis and lysosome related genes (phg1A, AlyA, B, C, D) (Perrin et al, 2015). In addition, consistent with the report that ESCRT plays an important role in membrane repair during M. marinum infection, many of the ESCRT components were induced .…”
Section: Marinum Infection Induces a Damage And Stress Response Insupporting
confidence: 83%
“…In this regard, both proximity ligation assay (Figures 5c and d) and subcellular immune-colocalization experiments ( Supplementary Figures S5A and S6) clearly demonstrated that amino acid starvation reduced the physical interaction of TM9SF4 with mTOR. Based on this, we speculated that TM9SF4, which is partially located in lysosome ( Figure 1c) and is known to modulate vesicular trafficking, 15 may promote mTOR dissociation from lysosome, causing its inactivation. However, this is highly speculative.…”
Section: Discussionmentioning
confidence: 95%
“…14 A recent study suggests that TM9SF4 could serve as intramembrane cargo receptors controlling vesicular trafficking, exocytosis and surface localization of glycine-rich membrane proteins. 15 Autophagy is a highly conserved process essential for cell survival under stress conditions including starvation, hypoxia and intracellular stress. 16 In cancer cells, autophagy is also an adaptive survival mechanism to overcome drug/acidic stressinduced cellular stress and cytotoxicity, including alteration of pH homeostasis.…”
mentioning
confidence: 99%
“…Generation of mNEET KO Cell Lines. We generated mNEET-knockout cell lines using the CRISPR/Cas9 method, as described previously (25). Briefly, a plasmid purchased from DNA2.0 was used, the guide RNA targeting the first exon of mNEET (AGCTCCAACTCCGCTGT*GCGAG; the * represents the cutting site of the Cas9 nuclease).…”
Section: Methodsmentioning
confidence: 99%